Tugurio de Dios : el barrio Lenin de Medellín (1969-1975) (2014)
ABSTRACT: This article explores the rise of informal settlements on the outskirts of Medellin between 1969 and 1975, through the case study of “Lenin” or “Francisco Antonio Zea” shantytown, known as Stage IV, according to the official nomenclature. It analyzes the ways in which residents tackled problems of housing and urban infrastructure and their relations with institutions, particularly the Municipal Administration and Instituto de Crédito Territorial (ICT) through their slum rehabilitation program. It also shows how the formation of the Lenin neighborhood was linked to a popular urban organization, the “Lenin Popular Committee”, promoted by Vicente Mejia, a revolutionary priest and advocate of urban struggles. Although these organizations have been visible in Colombia since the 1960s, they have been the subject of few historical studies. This article is therefore intended as a contribution to the study of the influence of these more or less autonomous experiences in the shaping of urban space.